WTO Procedures to Monitor RTAs. (2017) - Acharya, Rohini
Abstract : Ten years ago, in December 2006, the WTO created a new Transparency Mechanism for Regional Trade Agreements, an early harvest of the Doha Development Round of trade negotiations. The objective was to try to understand RTAs better and permit the Committee on Regional Trade Agreements (CRTA) to perform one of its key functions of monitoring RTAs in a more efficient manner.